A Permeable Cuticle, Not Open Stomata, Is the Primary Source of Water Loss From Expanding Leaves - Kane, Cade N.; Jordan, Gregory J.; Jansen, Steven; McAdam, Scott A. M. (Frontiers in Plant Science, 2020)
High rates of water loss in young, expanding leaves have previously been attributed to open stomata that only develop a capacity to close once exposed to low humidity and high abscisic acid (ABA) levels. To test this model, we quantified water loss through stomata and cuticle in expanding leaves of Quercus rubra. Stomatal anatomy and density were observed using scanning electron microscopy. Leaves of Q. rubra less than 5 days after emergence have no stomata, therefore water loss from these leaves must be through the cuticle. Once stomata develop, they are initially covered in a cuticle and have no outer cuticular ledge, implying that the majority of water lost from leaves in this phase of expansion is through the cuticle. Foliar ABA levels are high when leaves first expand and decline exponentially as leaves expand. Once leaves have expanded to maximum size, ABA levels are at a minimum, an outer cuticular ledge has formed on most stomata, cuticular conductance has declined, and most water loss is through the stomata. Similar sequences of events leading to stomatal regulation of water loss in expanding leaves may be general across angiosperms.